The relationship between organizational supports and employees’ retention at Takaful Ikhlas Sdn Bhd / Cahaya Sabarina Muajam and Nur Amalina Hussin - Muajam, Cahaya Sabarina; Hussin, Nur Amalina (Faculty of Business and Management, 2013)
Employee retention is the situation when the employees are stay longer for a long time of period in the organization. Organization has to compete to get or retain the most knowledgeable and skilled employees. At the same time if organization can’t aware have their employee’s needs and wants turnover will occur. This study explored the relationship between organizational supports and employees’ retention at Takaful Ikhlas Sdn Bhd. There are four dimensions under the organizational supports which are compensation and benefits, training and development, work environment and supervision. A total of 110 respondents were selected through convenience sampling. The level rate of employee’s retention in an organization is moderate which the mean is 2.93. Meanwhile, only three dimensions that have a significant relationship with employee’s retention. From the result, we can conclude that the compensation and benefits, work environment and supervision are the important factors that make the employees stay in the organization. These findings suggest the organization to improve the strategies in retaining the employees in the company that focuses on compensation and benefits that the company offers to their employees, work environment that the organization need to provide to them and also supervision that give the direct effect to perform their task effectively.